The efficacy of different treatment programs on myofascial pain - (:unkn) unknown (MONDUZZI EDITORE, 1996)
Myofascial pain syndrome (MPS) is characterized by regional musculoskeletal pain complaint arising from trigger points (TPs) within the belly of the muscles and pain is referred to other regions of body by applying pressure on these TPs. The aim of this study is to investigate the effects of different exercise programs on myofascial pain. Twenty-three female and seven male patients were selected for the study (mean age 35+/- 10.5). After a standard physical therapy program, passive stretching was applied on affected muscles of 15 patients and active exercise program of the shoulder girdle and neck mucles was added to the other 15 patients. Pain was evaluated by visual analoug scale (VAS), face scale and numerical pain scale. We detected statistically significiant decrease of pain values before and after the treatment in both groups (p<0.001). But there was no statistically significiant decrease of pain between the two groups on which the different exercise program were added to their physical therapy programs. As a result we suggest that both passive stretching and active exercise programs are effective on myofascial pain, but there is no superiority to each other.